Homicídios e eleições: um estudo sobre a influência das eleições municipais sobre taxas de homicídio através da abordagem de regressão descontínua - Silva, Robinson Aparecido da (2016)
The purpose of this dissertation is to investigate the relationship between electoral cycles and violent crimes in Brazilian municipal elections. It was used the Regression Discontinuity Designs (RDD) with the main goal of identifying a casual relation between tight elections in municipalities with more than 200 thousand voters and homicide rates during the second round of municipal elections from 1996 to 2012. The RDD was essentially used to analyze the rates of violent crimes during the second round in municipalities that had or not the second round. The empirical results did not identify any casual relation between tight elections and homicides. Therefore, from the research done, it is not possible to conclude that electoral cycles have effects in violent crimes in Brazil.